Dr. David Lysecki - Dhillon, Dalraj; Zhang, Eric; Wang, James; Lynn, Matthew (The Meducator, 2022)
Pediatric palliative care is often an overlooked field of medicine. As terminally ill children make up a small proportion of patients in Canada, a less robust network of resources is available to deliver end-of-life care for these patients. To gain a better insight into this field, we sat down with Dr. David Lysecki, a pediatric palliative care physician at McMaster Children’s Hospital. He is also the founder and head of the Quality of Life & Advanced Care program at McMaster Children’s Hospital and the Division of Pediatric Palliative Medicine in the McMaster University Department of Pediatrics.